Knowledge as global public good: Universities as drivers of inclusive development in the Global South - Andres, Mercedes Victoria (Journal of International Students, 2026)
This article examines higher education and knowledge as Global Public Goods from a Global South perspective, arguing that their roles in development, inclusion, and innovation cannot be fully understood through dominant liberal internationalization frameworks shaped in the Global North. It asks how knowledge and internationalization can be rethought to challenge academic dependency and reposition universities as infrastructures for inclusive development. Using a Global Public Goods framework, the analysis focuses on four dimensions: (a.) trajectories of internationalization, (b.) universities as catalysts for development, (c.) student mobility and repatriation as mechanisms to convert mobility into domestic capacity, and (d.) state leadership and public financing in higher education, science, and technology. Drawing on qualitative analysis from China, Argentina, and Brazil, the study finds that state investment strengthens research capacity, while internationalization remains tied to Global North circuits of recognition. It concludes that recentering knowledge as a Global South public good is essential to reposition universities for equitable, sovereign, and development-oriented internationalization.